Review and Meta-Analysis of PPR in Goat and Sheep of Bangladesh from 2000 to 2019 - F. M. Yasir Hasib; Sharmin Chowdhury (Turkish Journal of Agriculture: Food Science and Technology)
Peste des petits ruminant (PPR), considered as goat plague is the most fatal infectious viral disease for small ruminants. This disease is endemic in many parts of the world including Bangladesh causes extensive loss on livestock and economy. This study was conducted to estimate the prevalence of PPR and this is the first meta-analysis on PPR as per authors knowledge in Bangladesh. Articles published during the years 2000 to 2019 on the topic PPR within three electronic databases were used for prevalence estimation by random effect meta-analysis model. A total of 39 articles were finally included in the model for prevalence estimation of goat and sheep. 1589784 goat and 142036 sheep were included in the study for analysis. Analysis showed prevalence of PPR was 15.17% (95% CI: 15.11-15.22) and 9.17% (95% CI: 9.02-9.32), respectively for goat and sheep. As PPR is affecting small ruminants in variable percentage in different districts of Bangladesh, this study estimates the cumulative prevalence of Bangladesh. This study may act as a baseline for taking effective control strategy of PPR in Bangladesh through proper allocation of resources on a priority basis.